The photography and the feeling: no sight and sensoriality (Revista Apotheke, 2020)
A Fotografia e o Sentir Project comprises teaching and photographic practice with students from IEACN - Institute of Education and Assistance to the Blind of the Northeast, located in the city of Campina Grande - PB. Its realization is anchored in the opportunity to expand research on accessibility and inclusion, also to develop didactic and methodological resources when disseminating photography to people with visual deficiencies. In the theoretical path by Vygotsky (1997), Duarte Júnior (2012) and Barbosa (2007). This study covers the use of multisensory for the construction of images, when exploring auditory and tactile stimuli in the production of photographs. This way, the text proposes a debate on the contributions of perception and feeling to the learning process and the importance of giving the blind student the role of emitter and creative source. In the contributions of Schafer (2003), Dubois (2012), Alves (2009) among others.
Keywords: Inclusion.; Visual impairment; Soundspace; Tactile perception; Photography